Endocytosis by antigen presenting cells: dendritic cells are as endocytically active as other antigen presenting cells. - Levine, T P (1992)
Although dendritic cells are the most potent of all antigen presenting cells, they have paradoxically been regarded as having only a minimal capacity for endocytosis, which is a crucial step in antigen processing prior to presentation. Previous studies of dendritic cells, which are only available in small numbers, have been restricted to measurement of long-term endocytosis and so have stressed lysosomal accumulation. Measurement of traffic through late endosomes, which are closely related to the organelle in which antigen processing occurs, has, to date, required large numbers of cells and therefore has not been possible for dendritic cells. To resolve the paradox for dendritic cells, we have developed a flow cytometric assay of fluid-phase endocytosis that assesses late endosomal traffic by kinetic analysis of exocytosis in small numbers of cells. Using this assay, we show that fluid-phase endocytosis--in particular, traffic through late endosomes--is as active in dendritic cells as in other antigen presenting cells.